2006
DOI: 10.1016/j.jbiomech.2005.01.012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of water removal on the strength and toughness of cortical bone

Abstract: Although the effects of dehydration on the mechanical behavior of cortical bone are known, the underlying mechanisms for such effects are not clear. We hypothesize that the interactions of water with the collagen and mineral phases each have a unique influence on mechanical behavior. To study this, strength, toughness, and stiffness were measured with three-point bend specimens made from the mid-diaphysis of human cadaveric femurs and divided into six test groups: control (hydrated), drying in a vacuum oven at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
257
3
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 311 publications
(281 citation statements)
references
References 31 publications
10
257
3
2
Order By: Relevance
“…As can be seen, dehydration causes an appreciable reduction of fracture energy, accompanied by a slight increase of elastic modulus, in agreement with earlier works (Currey, 1988a;Lucksanasombool et al, 2001;Nyman et al, 2006;Wang and Agrawal, 1996). The vascular porosity (Table 3) can be used to estimate the content of free water.…”
Section: Resultssupporting
confidence: 89%
“…As can be seen, dehydration causes an appreciable reduction of fracture energy, accompanied by a slight increase of elastic modulus, in agreement with earlier works (Currey, 1988a;Lucksanasombool et al, 2001;Nyman et al, 2006;Wang and Agrawal, 1996). The vascular porosity (Table 3) can be used to estimate the content of free water.…”
Section: Resultssupporting
confidence: 89%
“…The interaction of mineral and collagen in bone is discussed from the concept of a mineral-reinforced collagen matrix, and there is an evidence for a mineral matrix with collagen inclusions [18][19][20][21][22]. The role of water in the overall behavior of bone is also considered important [23]; however, the underlying mechanism is still not clearly understood. The compressive strength of bulk cortical bone in humans is around 170 MPa for the femur, and the elastic compressive modulus is around 17 GPa [24].…”
Section: Strength Of Bonementioning
confidence: 99%
“…A number of early studies demonstrated that dehydration decreases the strain at fracture and energy to fracture of cortical bone [6][7][8][9][10][11], and a recent study found that the contribution of water to bone toughness exists at multiple energy levels [12]. It has been shown that elevated drying of bone (70 °C) can cause significantly greater loss of bone toughness than moderate drying (room temperature), indicating that each of the hierarchical arrangements of water molecules bound to the collagen and mineral phases would likely influence the ability of bone to resist fracture.…”
Section: Introductionmentioning
confidence: 99%